2014
DOI: 10.1111/jsm.12353
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Sex Hormones and Erectile Dysfunction in Male Taiwanese Participants with Obesity

Abstract: Introduction Obesity has been receiving an increasing amount of attention recently, but investigations regarding the potential impact of obesity, sexual behaviors, and sex hormones on erectile dysfunction (ED) in men have not completely clarified the association. Aim To identify the relationship between ED, sexual behavior, sexual satisfaction, sex hormones, and obesity in older adult males in Taiwan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 52 publications
2
3
1
Order By: Relevance
“…Our results were in accordance with our previous cross‐sectional study, in which FT and BT were found to be inversely related to worsening ED. Moreover, the associations between low FT, BT, and ED were also observed in other previous studies [17,32]. Interestingly, the Olmsted County study, a cross‐sectional community‐based study, provided an age‐related mechanism that suggested that age‐related decline of BT levels led to decreased sexual function by specific biologic pathway [10].…”
Section: Discussionsupporting
confidence: 71%
“…Our results were in accordance with our previous cross‐sectional study, in which FT and BT were found to be inversely related to worsening ED. Moreover, the associations between low FT, BT, and ED were also observed in other previous studies [17,32]. Interestingly, the Olmsted County study, a cross‐sectional community‐based study, provided an age‐related mechanism that suggested that age‐related decline of BT levels led to decreased sexual function by specific biologic pathway [10].…”
Section: Discussionsupporting
confidence: 71%
“…Low levels of free testosterone have been associated with ED [27][28][29]. Contrary to our expectations, the free testosterone levels were not associated with IIEF scores after correcting for confounding factors.…”
Section: Discussioncontrasting
confidence: 86%
“…Only 6.8% of patients in this study had been assessed within a team-based model prior to presentation at SDSM or MCWHC. 2 , 15 The purpose of this study was to assess whether the multi-disciplinary model demonstrated benefits in the form of enhanced patient satisfaction. At a time when provider reimbursement is based on Hospital Consumer Assessment of Healthcare Providers and Systems scores, patient satisfaction becomes the leading metric for compensation.…”
Section: Discussionmentioning
confidence: 99%